Mitigation of industrial hazards by water spray curtains. (November 2017) - Buchlin, Jean-Marie
Abstract: A Nowadays, the water spray curtain is recognized as a useful technique to mitigate major industrial hazards. It combines attractive features such as simplicity of use, efficiency and adaptability to different types of risks. In case of accidental toxic gas releases, the spray curtain may be used as a direct-contact reactor exchanging momentum, heat and mass with the gas phase. The cloud is diluted, warmed, and if toxic, some of its toxic content can be absorbed by the droplets to which chemical reactants can be added. In case of fire, water sprays can provide thermal shielding to maintain the integrity of storage tanks. The curtain behaves as a filter and can produce significant attenuation of the incident radiation that impinges on crucial structures such as petro-chemical storage tanks. Both of these applications have been thoroughly investigated at the von Karman Institute The outcome of these research projects is a comprehensive engineering code simulating on the one hand the forced dispersion, heating and physico-chemical inhibition of cold pollutant clouds and on the other hand the thermal shielding performance of a water curtain. The numerical approach is supported by laboratory (including wind tunnel tests) and field tests dedicated to investigate the effects of numerous operating parameters on the water spray curtain efficiency and to build a data base for model validation. The paper gives an overview of the main features of the modeling and on practical industrial applications with a special focus on the adequate water curtain operating conditions and the influence of environmental factors. Highlights: The paper deals with the modelling and practical industrial applications of water curtain used as a mitigation means. In case of accidental toxic gas releases, the spray curtain may dilute, warm and in some conditions absorb the pollutant of the cloud. In case of fire, water sprays can provide thermal shielding to maintain the integrity of storage tanks. The curtain behaves as a filter and can produce significant attenuation of the incident radiation that impinges on crucial structures such as petro-chemical storage tanks. The emphasis is given to operating conditions and influence of environmental factors on the performance of the water curtain.